Risk Factors And Surgical Outcomes Of Diabetic Foot Ulcer In Patients With Type 2 Diabetes- A Retrospective Study - Ram, Ramkrit; Kumari, Deepa; Kumar Verma, Dhananjaya; Singh, Swatantra (Journal of Neonatal Surgery, 2025)
Introduction- Diabetic foot ulcers (DFUs) are a major complication of type 2 diabetes, leading to severe morbidity, infections, and amputations. Identifying risk factors and surgical outcomes is crucial for improving patient management. This retrospective study analyzes key predictors of DFU progression and evaluates surgical interventions to optimize treatment strategies and outcomes. Material and method- This retrospective study analyzed medical records of patients with type 2 diabetes and DFUs treated at Maharshi Vishwamitra Autonomous State Medical College, Ghazipur. Data on demographics, comorbidities, ulcer characteristics, infection status, surgical interventions, and outcomes and its predictors were collected. Statistical analysis, including multivariate regression, was performed to identify significant risk factors influencing DFU progression and surgical outcomes. Result- This study analyzed 980 patients with mean age of 54.8±10.7years and mean diabetes duration of 12.5±6.8years). Poor glycemic control was present in 68%, with neuropathy (76.5%), peripheral arterial disease i.e. PAD (48%), and CKD (36%) as major comorbidities. Infected ulcers were observed in 65%, osteomyelitis in 40%, and multidrug-resistant organisms in 22%. Surgical interventions included wound debridement (74%), minor amputations (32%), and major amputations (34%). Postoperative infections (28%) and delayed healing (39%) were common, with a 48% re-ulceration rate. Multivariate analysis identified osteomyelitis, PAD, and uncontrolled diabetes as significant predictors of poor outcomes. Conclusion- Diabetic foot ulcers are associated with significant comorbidities, poor glycemic control, and high infection rates, leading to severe surgical outcomes. Early intervention, optimized diabetes management, and multidisciplinary care are crucial in reducing complications, improving limb salvage, and enhancing the overall prognosis for affected patients.